Interaction of Schistosoma mansoni Sporocysts and Hemocytes of Biomphalaria - D. Negrão-Corrêa; A. C. A. Mattos; C. A. J. Pereira; R. L. Martins-Souza; P. M. Z. Coelho (Journal of Parasitology Research)
Human infection by Schistosoma mansoni affects more than 100 million people worldwide, most often in populations of developing countries of Africa, Asia, and Latin America. The transmission of S. mansoni in human populations depends on the presence of some species of Biomphalaria that act as an intermediate host. The compatibility between S. mansoni and its intermediate host is influenced by behavioral, physiological, and genetical factors of the mollusc and the parasite. The susceptibility level of the mollusc has been attributed to the capacity of internal defense system (IDS)—hemocytes and soluble components of the hemolymph—to recognize and destroy the parasite, and this will be the center of interest of this paper. The schistosome-resistant Biomphalaria can be an alternative strategy for the control of schistosomiasis.